Simulasi Pinjaman Daerah sebagai alternatif pilihan Pembiayaan Pembangunan Infrastruktur di Kabupaten Batang Hari - Sri Rosmawati; Muryati Muryati (Universitas Batanghari Jambi, 2023)
Regional Loans are one of the alternative sources of financing in the Regional Revenue and Expenditure Budget to fund activities that are initiatives of the Regional Government in the framework of Local Government affairs based on the provisions of laws and regulations. Regional loans can be used to finance infrastructure and/or investment in regional infrastructure and facilities in the framework of public services. In addition, Regional Loans can also be used to cover regional cash flow. This study aims to determine the financial capability of the Batang Hari Regency Government and determine the number of feasible loans if the Batang Hari Regency Government makes regional loans as an alternative to financing infrastructure development. The data used in this study is secondary time series data derived from the Batang Hari Regency Government Budget Realization Report for the 2017-2021 period. The analysis tools used are the ratio of regional financial ability to repay loans with the Debt Service Coverage Ratio (DSCR), the Maximum Loan Limit (BMP) and to determine the amount of loans that can be made by regions in 2017-2021 by calculating regional revenue plans and regional spending plans, which are carried out using the Trend analysis method. Based on the simulation result conducted, the Batang Hari Regency Government has a Debt Service Coverage Ratio (DSCR) value of 4.81 which exceeds the minimum standard set at 2.5. The results of the analysis also show a Maximum Loan Limit of Rp. 740,070,216,978. Based on data obtained in fiscal year 2021. When viewed from the projection results, the loan that can be obtained by the Regional Government of Batang Hari Regency according to the analysis of the BMP Maximum Loan Limit in 2022 is IDR 706,263,200,215. Net funds are obtained from the projected results for 2022 of Rp. 503,718,603,808 and the maximum installments that can be prepared are Rp. 201,487,441,523.